PERFORMANCE KINERJA DOSEN DI LINGKUNGAN UNIVERSITAS RIAU KEPULAUAN DITINJAU DARI ASPEK SUPERVISI DEKAN PADA TAHUN AKADEMIK 2012-2013 - Efendi, Yarsi (Universitas Riau Kepulauan, 2014)
This research is intended to find out the effectively influence of Dean’s Supervision on Lecturer’s Work Performance of Universitas Riau Kepulauan Batam. Academic year 2012-2013. The population of this research were all 120 lecturers of Universitas Riau Kepulauan Batam. Academic year 2012-2013. This research used total sampling technique and all 120 members of population are taken to respondents. The collection of the data of this research used questionnaire. The data analysis technique used linier regression with level significantly is 5 %.The result of the research showed that the effectively influence of Dean’s Supervisision have positive and very significant on effort to Lecturer’s Work Performance of Universitas Riau Kepulauan Batam on academic year 2012-2013 . Effective contribution of dean’s supervision had 22,6%. It is mean 73,4% simultaneously contributing of another factors.